TRANSPORT SYSTEM OF THE DIGITAL SOCIETY: PROBLEMS AND SOLUTIONS - T. A. Rudakova; O. Yu. Rudakova (Стратегические решения и риск-менеджмент)
In a transition economy, the issues of reforming the transport system and overcoming the exacerbating problems of industry management become relevant. It seems that technological progress and the digital transformation of business processes should simplify the algorithm of action in management matters. However, as practice shows, during this period new conditions for the functioning of the industry arise (the emergence of new modes of transport or their modification) and elements of the transport system undergo changes. A more serious problem, according to the authors, is the unpredictability of foreign partners’ behaviour in relation to exclusive rights to software (SW) used by companies in the transport and logistics sector. The purpose of the study is to develop a model for assessing the cost of the risk of a company's sudden transition to domestic software and test it on the materials of companies in the transport and logistics industry of Altai Krai. The study was conducted in the context of trends in the digital transformation of the transport system, identifying factors and types of risk, and assessing their impact on the information technology landscape (IT landscape) of transport companies in the context of sanctions. The results confirm the need to prepare industry participants homegrown software and to minimise potential risks. A sudden software replacement is more likely to cause serious financial loss to organisation than planned actions that do not disrupt business processes and communications with partners and government agencies. The practical significance of the proposed risk assessment model lies in the possibility of its application when making management decisions on the digitalisation of business processes and the transition to domestic software, regardless of the industry and size of the company.